Information Model for Supervision Management in the Cooperative Education for Higher Education Institutions in Thai Supply Chain - Artaphon Chansamut (ExcelingTech, 2023)
This research study was to develop and to evaluate an appropriate about information model for supervision management in the cooperative education for higher education institutions in Thai supply chain. The sample consisted of ten experts on supply chain. Data analysis was the average mean and standard deviation. The research tool was questionnaire about information model for supervision management in the Cooperative Education for higher education institutions in Thai supply chain comprises five main components, namely suppliers, manufacturer, Education customers, Consumers. The results from ten experts agreement of about information model for supervision management in the cooperative Education for higher education institutions in Thai supply chain was a high level which means that model can develop information model for supervision management in the cooperative Education for higher education institutions in Thai sustainable supply chain.